2019
DOI: 10.1038/s41562-019-0654-y
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of paternal investment predict cross-cultural variation in jealous response

Abstract: Long-lasting, romantic partnerships are a universal feature of human societies; but almost as ubiquitous is the risk of instability when one partner strays. Jealous response to the threat of infidelity is well-studied, but most empirical work on the topic has focused on a proposed sex difference in the type of jealousy (sexual or emotional) men and women find most upsetting, rather than on how jealous response varies 1,2. This stems in part from the predominance of studies using student samples from industrial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 27 publications
0
32
0
Order By: Relevance
“…The available evidence documented in the review suggests substantial variation in the frequency with which RJ or infidelity was cited as a reason for IPV. This may be due in part to differing cultural attitudes towards RJ and infidelity [129], and IPV [130]. More research is needed to determine whether the mechanisms and pathways identified in this review are upheld across different regions (e.g., the Middle East and North Africa) and countries, as well as among different populations within countries.…”
Section: Gaps In the Literaturementioning
confidence: 96%
“…The available evidence documented in the review suggests substantial variation in the frequency with which RJ or infidelity was cited as a reason for IPV. This may be due in part to differing cultural attitudes towards RJ and infidelity [129], and IPV [130]. More research is needed to determine whether the mechanisms and pathways identified in this review are upheld across different regions (e.g., the Middle East and North Africa) and countries, as well as among different populations within countries.…”
Section: Gaps In the Literaturementioning
confidence: 96%
“…CHEATER; Cosmides, Barrett, & Tooby, 2010) and culturally evolved lexical descriptors for communicating about peoples’ reputations or current behavioural states (e.g. ‘unreliable’; Buss, 2011; Fiddick et al, 2016: Kallens et al, 2018; Scott–Phillips, 2014). Although research based on hypotheses about difference–detecting adaptations is in its infancy, this theoretical lens provides important links between traditional lexically based personality research and the evolutionary psychological approach advocated in this paper.…”
Section: An Adaptationist Framework For Personality Science: Prospectmentioning
confidence: 99%
“…We focus here not on the phylogeny of friendship jealousy, but rather on the features that it might have if, like romantic jealousy, it functioned to help maintain valued but potentially threatened social bonds. maintenance of those relationships-romantic jealousy is likely one adapted tool of partner retention (e.g., Buss, 2000Buss, , 2013Buss & Haselton, 2005;Daly et al, 1992;Scelza et al, 2019;Symons, 1979). 3 Behavior consistent with romantic jealousy may be evidenced in some nonhuman animals; among humans, it exists across cultures, and it possesses features that appear to be well-designed to solve the recurrent problem of retaining mates in the face of third-party threats: (a) romantic jealousy is evoked by cues that a romantic partner stands to be lost to a third party; (b) cues with better predictive validity of impending loss receive prioritization in driving levels of romantic jealousy; and (c) romantic jealousy spurs a suite of behavioral inclinations, known as mate guarding, that are theoretically aimed at countering the threat of partner loss (Buss, 2000(Buss, , 2013Buss & Haselton, 2005;Buss et al, 1992;Buss & Shackelford, 1997;Buunk, 1997; Lewis et al, 2016;Scelza, 2014;Scelza et al, 2019;Schmitt & Pilcher, 2004).…”
Section: Jealousy Can Protect Valued Social Relationshipsmentioning
confidence: 99%